EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN PADA MATERI SISTEM GERAK DALAM PEMBELAJARAN IPA - Nanik Syafiratul Jannah; Aisyah Az Zahra; Febbi Imelliya; Muhammad Swignyo Prayogo (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to determine the effectiveness of using learning media in teaching motion systems in science education. The problem behind this study is the low learning outcomes of students and their lack of understanding of abstract motion system concepts due to the limitations of the learning media used by teachers. The research method used is a literature review with a descriptive qualitative approach. Data were obtained from ten relevant scientific articles and analyzed based on topic relevance, types of media used, and learning outcomes achieved. The results of the analysis show that various types of media, such as learning videos, digital applications, educational games, visual media, and concrete teaching aids, have been proven effective in improving student learning outcomes, motivation, and active participation. These media help students understand the concept of motion systems in a more concrete, interactive, and interesting way. Thus, the use of innovative learning media that suits the characteristics of students can create active, contextual, and meaningful science learning.